2020
DOI: 10.1002/pbc.28502
|View full text |Cite
|
Sign up to set email alerts
|

A single‐arm study of systemic and sub‐Tenon chemotherapy for Groups C and D intraocular retinoblastoma: A Children's Oncology Group study (ARET 0231)

Abstract: Background Eyes with Group D intraocular retinoblastoma have low salvage rates. A pilot study showed safety and efficacy of sub‐Tenon's fascia carboplatin with systemic chemotherapy supporting further study. Methods Children with newly diagnosed bilateral intraocular retinoblastoma with at least one remaining Group C or D eye were treated with six courses of carboplatin/etoposide/vincristine (CEV) with sub‐Tenon's fascia carboplatin for Group C/D eyes during courses 2‐4. Local ophthalmic therapy started at cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The studies on higher dose carboplatin-based chemotherapy for advanced intraocular or extraocular retinoblastoma are summarized in Table 4. [5][6][7]11,[15][16][17][18] As is apparent, the prevailing evidence is largely from single-arm or retrospective studies. It prompted us to study a head-to-head compar- group E retinoblastoma undergoing enucleation following neoadjuvant chemotherapy are treated with a total of six cycles of standard-dose chemotherapy in the authors' unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies on higher dose carboplatin-based chemotherapy for advanced intraocular or extraocular retinoblastoma are summarized in Table 4. [5][6][7]11,[15][16][17][18] As is apparent, the prevailing evidence is largely from single-arm or retrospective studies. It prompted us to study a head-to-head compar- group E retinoblastoma undergoing enucleation following neoadjuvant chemotherapy are treated with a total of six cycles of standard-dose chemotherapy in the authors' unit.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence is scarce for the role of higher dose carboplatin‐based chemotherapy in improving ocular and vision salvage for group D or E retinoblastoma. The studies on higher dose carboplatin‐based chemotherapy for advanced intraocular or extraocular retinoblastoma are summarized in Table 4 5–7,11,15–18 . As is apparent, the prevailing evidence is largely from single‐arm or retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to salvage the globe with systemic intravenous chemotherapy were successful in approximately 50% of patients with group D disease 1–7 . Increasingly, efforts to cure the child and save the globe have rapidly evolved to local delivery techniques like periocular carboplatin in conjunction with systemic chemotherapy as well as IA therapies 5,8,9 . At the time of initiation of this study, retrospective data from single institutions had reported promising results of the intra‐arterial technique of delivering chemotherapy to the eyes of children with retinoblastoma via the ophthalmic artery 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Increasingly, efforts to cure the child and save the globe have rapidly evolved to local delivery techniques like periocular carboplatin in conjunction with systemic chemotherapy as well as IA therapies. 5,8,9 At the time of initiation of this study, retrospective data from single institutions had reported promising results of the intra-arterial technique of delivering chemotherapy to the eyes of children with retinoblastoma via the ophthalmic artery. [9][10][11][12] This technique is a variation of the original intra-arterial technique used by Japanese investigators.…”
Section: Introductionmentioning
confidence: 99%